2015
DOI: 10.2320/matertrans.m2014396
|View full text |Cite
|
Sign up to set email alerts
|

Damage Evaluation in Lithium Cobalt Oxide/Carbon Electrodes of Secondary Battery by Acoustic Emission Monitoring

Abstract: Acoustic Emission (AE) technique was employed for evaluating charge/discharge damage in a lithium-ion battery. A coin-type battery of lithium cobalt oxide/carbon electrodes was used for acoustic monitoring during accelerated charge/discharge cycle test. A number of AE signals were successfully detected during charge/discharge. Microstructural observation of the electrodes after the cycle test revealed mechanical damage such as micro-cracking of the cathode and chemical damage such as solid electrolyte interpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
5
32
1
Order By: Relevance
“…For example, experiments on LiCoO 2 observed a somewhat steady number of acoustic events during cycling, while other experiments measured a large number of acoustic events in the first cycle followed by a much lower rate in later cycles . Other work on this system found that a bimodal distribution in the acoustic event frequency versus amplitude, and attributed some events to cracking and other events to gas bubble nucleation during solid electrolyte interphase formation . The occurrence of cracking events was somewhat constant with cycle number in their experiments, while bubble nucleation accounted for the majority of the first‐cycle acoustic events.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, experiments on LiCoO 2 observed a somewhat steady number of acoustic events during cycling, while other experiments measured a large number of acoustic events in the first cycle followed by a much lower rate in later cycles . Other work on this system found that a bimodal distribution in the acoustic event frequency versus amplitude, and attributed some events to cracking and other events to gas bubble nucleation during solid electrolyte interphase formation . The occurrence of cracking events was somewhat constant with cycle number in their experiments, while bubble nucleation accounted for the majority of the first‐cycle acoustic events.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have utilized acoustic emission to understand the evolution of damage in these materials, but the results and conclusions vary. For example, experiments on LiCoO 2 observed a somewhat steady number of acoustic events during cycling, while other experiments measured a large number of acoustic events in the first cycle followed by a much lower rate in later cycles . Other work on this system found that a bimodal distribution in the acoustic event frequency versus amplitude, and attributed some events to cracking and other events to gas bubble nucleation during solid electrolyte interphase formation .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same applies to the AE 2 hits, which according to literature lie at the border of acoustic activity between gassing and cracking. [40,42,59,62] Because the acoustic activity in the frequency range of AE 2 also decreased to a minor fraction after the initial cycle, we assign it to cSEI formation. Similar results that contradict the classical assignment of AE signals to gassing were observed in the investigation of silicon anodes and deposition of calcium carbonate and zinc phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Kircheva et al used AE to probe the solid-electrolyte interphase (SEI) formation and lithium intercalation into the bulk of graphite electrodes. [39] Moreover, Choe et al analyzed damage mechanisms in lithium cobalt oxide (LiCoO 2 , LCO) and graphite electrodes by classifying AE signals into distinct types, [40] and Villevieille et al investigated conversion-type reactions in NiSb 2 electrodes. [41] Other LIB materials, such as silicon and metal hydrides, have also been studied; yet, Ni-rich layered oxide cathode materials have not been examined to date.…”
Section: Introductionmentioning
confidence: 99%